Penerapan Media Pembelajaran Teknik Dasar Passing Sepakbola Berbasis Android Di SMPN 3 Cikarang Utara - Fajri Setiawan; Ine Rahayu Purnamaningsih; Ardawi Sumarno (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this research is to find out the application of Android-based Android-based Learning Media for Football Passing at SMPN 3 Cikarang Utara. This type of research is descriptive quantitative. The method used is a one group pretest-posttest type experiment (single group initial test-end test). The sample using purposive sampling method explains that purposive sampling is a technique to determine samples with certain considerations. In this case, the writer took a sample of class VII.8 which found 40 students at SMPN 3 Cikarang Utara. In this study, it was successful to show the results of the study, it can be seen that the application of android-based learning media for class VII.8 students to basic soccer techniques is in the very good category by 15%, in the good category by 70%, and in the sufficient category by 15%. Based on the results of this study, it can be interpreted that the application of learning media for basic football passing techniques based on Android is mostly in good category. The key to the application of android-based basic passing technique learning media at SMPN 3 Cikarang Utara is good, namely 70%. Keywords : Learning Media, Basic Passing Techniques, Football, Android Based